Wartime Dissent in America A History and Anthology - Mann, R.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
Through the speeches, essays and interviews of some of the most compelling individuals in American history who stood against the key conflicts of their lifetimes, this book gives remarkable insight into wartime dissent in the U.S. from the revolutionary war to the war on terror.
Keywords: Civilization—History.; America—History.; United States—History.; Social history; Sociology; Military history; Cultural History; History of the Americas; US History; Social History; Sociology, general; History of Military